The ratio of Indonesia BMKG agency and TRMM satellite Rainfall Data in West Java Province by Using Statistical Parameter and Correlation Analysis - Rian Alfian; Ahmad Zakaria; Endro Prasetyo Wahono; Dyah Indriana Kusumastuti; Ahmad Herison (Journal of Engineering and Scientific Research, 2021)
Weather observations can be done in two ways, namely weather observations based on weather stations and based on remote sensing such as satellites. One of these weather study data is rainfall measured from the BMKG rain observation post and TRMM satellite observations. To see the pattern of the distribution of rain that has occurred, the two weather observations can be connected as a reference for the distribution of rain. The purpose of this study was to analyze the correlation value of rainfall data between BMKG and TRMM by looking at the comparison graph and analyzing the comparison of statistical parameters. This research was conducted using daily rainfall data from 1998-2018 at four rain stations in West Java Province and taking descriptive decisions in the form of pictures and graphs in the form of daily, monthly and annual data. Based on the analysis results, the largest correlation value is in the annual cumulative with a value of 0,88-0,94, the smaller the number of days, the smaller the correlation value. The BMKG and TRMM rainfall data have relatively the same pattern, but the maximum data have differences so that it reduces the correlation value. In the Statistical Parameter analysis, it can be stated that the difference in the values ??of the statistical parameters is directly proportional to the daily cumulative, that the difference in the median and mean values ??in the BMKG and TRMM data is greater in the data with a larger cumulative. Meanwhile, for linear regression analysis, it was found that the greatest value was the cumulative 1-year value with a coefficient of determination from 0,78 - 0,89.